2002
DOI: 10.1111/j.1520-037x.2002.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High‐, Moderate‐, and Low‐Fat Diets on Weight Loss and Cardiovascular Disease Risk Factors

Abstract: Over 60% of Americans are overweight and a number of popular diets have been advocated, often without evidence, to alleviate this public health hazard. This study was designed to investigate the effects of several diets on weight loss, serum lipids, and other cardiovascular disease risk factors. One hundred men and women followed one of four dietary programs for 1 year: a moderate-fat (MF) program without calorie restriction (28 patients); a low-fat (LF) diet (phase I) (16) ; a MF, calorie-controlled (phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…Similarly, Volek et al 43 did not observe changes in homocysteine after 4 kg of weight loss on a reduced fat diet, with vitamin/mineral supplements including folic acid. Similarly, Fleming 44 in a study of 100 men and women, found no significant effect of weight loss in homocysteine. In crosssectional studies, folate was found to have a greater effect on endothelial function than homocysteine.…”
Section: Homocysteine and Folatementioning
confidence: 92%
“…Similarly, Volek et al 43 did not observe changes in homocysteine after 4 kg of weight loss on a reduced fat diet, with vitamin/mineral supplements including folic acid. Similarly, Fleming 44 in a study of 100 men and women, found no significant effect of weight loss in homocysteine. In crosssectional studies, folate was found to have a greater effect on endothelial function than homocysteine.…”
Section: Homocysteine and Folatementioning
confidence: 92%
“…31 The importance of raising HDL-C in reducing cardiovascular and stroke risk has also been highlighted in recent reviews. 3,32 Raising Serum HDL-C Raising serum HDL-C can decrease cardiovascular risk by 5.5% for each 1 mg/dL increment in baseline HDL-C. 33 There are various pharmacological and nonpharmacological means to increase serum HDL-C. 34 Lifestyle-associated improvement in HDL-C appear to be greatest in persons with the highest baseline HDL-C levels (Ն60 mg/dL). 35 Many of these lifestyle modifications have been shown to reduce overall stroke risk, but it is unclear what effect they will have in patients with low-HDL at the highest risk of cardiovascular disease.…”
Section: Treatment Strategies Current Guideline Recommendationsmentioning
confidence: 99%
“…If a person is consuming below this threshold, then triglyceride will be broken down from adipose tissue to generate ketones to supply the CNS. Most of the small feasibility studies showed that LCKD compliance in a clinical outpatient setting showed promise for weight loss, so more formal randomized, controlled trials (RCTs) were justified [39][40][41][42][43][44].…”
Section: Low-carbohydrate Ketogenic Diet and Obesity Studiesmentioning
confidence: 99%